Translation Techniques In Bilingual Beauty Product Advertisements - Primayani, Ni Putu Rahayu; Maharani, Sang Ayu Isnu; Udayana, I Nyoman (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The growth of the beauty industry has led to the increased use of bilingual advertisements to reach a broader audience. However, the differences in cultural and linguistic contexts between the source and target languages of the advertisements often lead to shifts in meaning. In this context, it is the translator's responsibility to act as a bridge to fill this gap. This research aims to identify and analyse the translation techniques used in bilingual beauty product advertisements and to examine how these techniques reflect translation equivalence. This research employs a qualitative method using the theory of translation techniques by Molina and Albir (2002) and the concept of translation equivalence by Nida and Taber (1969). The data were collected from bilingual beauty product advertisements sourced from the official YouTube channel of Maybelline New York. Data were collected through documentation and note-taking techniques and then analysed by comparing English and Indonesian subtitle transcripts to identify the applied translation techniques and the type of equivalence achieved. The results were presented with a formal method through the use of table and informal method to describe the analysis. The findings revealed that eleven out of eighteen translation techniques were used, discursive creation, borrowing, linguistic compression, modulation, amplification, literal translation, linguistic amplification, reduction, transposition, adaptation, and generalization. The application of these techniques primarily achieved dynamic equivalence. Meanwhile, formal equivalence was achieved when the source and target language structures closely aligned.